Reflection-impulsivity in athletes: A cross-sectional and longitudinal investigation. Issue 10 (3rd October 2021) - Vaughan, Robert S.; Hagyard, Jack D.; Edwards, Elizabeth J.; Jackson, Robin C.
Abstract: Reflection-impulsivity is a dimension of cognitive or decision-making style. We conducted two quasi-experimental studies to examine reflection-impulsivity in athletes using an information sampling task. In Study 1 ( n  = 108; Mage   = 22.7 ±  SDage  = 1.42; 50% female), we used a cross-sectional design to compare performance across athletic expertise (super-elite, elite, amateur, novice or non-athlete) and sport type (external-paced or self-paced). In Study 2 (Time 1 n  = 106; Mage   = 21.32 ±  SDage  = 5.77; 53% female and Time 2 n  = 64; Mage   = 21.19 ±  SDage  = 5.12; 44% female), we examined changes in reflection-impulsivity across a 16-week playing season. Study 1 showed more accurate and more efficient performance as athletic expertise increased. Study 2 revealed better effectiveness and efficiency following sport participation, a 16-week playing season, most notably in elite-level performers. No sport-type differences were noted. Taken together, the studies demonstrate an association between reflection-impulsivity and athletic expertise, while also providing evidence that competitive sports participation leads to efficient decisions based on reflection, without sacrificing accuracy, which is often a consequence of impulsive decision-making.